The Experience of Retirement - Weiss, Robert Stuart, 1925- (Book collections on Project MUSE., 2005)
"In The Experience of Retirement, Robert S. Weiss provides a detailed description of how some people plan their retirement, what life in retirement is like, and what makes for a fulfilling retirement. His book can thus serve as a most useful guide. Weiss shows us both retirement's benefits and its possible costs, both the relief retirees can feel once free of work's stresses and constraints and the discomfort that can be caused by loss of the positive aspects of working life."--Jacket